2015
DOI: 10.1021/acs.jpcb.5b10747
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Computation of the Basal kon using Direct Simulation of Protein–Protein Association with Flexible Molecular Models

Abstract: An essential baseline for determining the extent to which electrostatic interactions enhance the kinetics of protein–protein association is the “basal” kon, which is the rate constant for association in the absence of electrostatic interactions. However, since such association events are beyond the milliseconds time scale, it has not been practical to compute the basal kon by directly simulating the association with flexible models. Here, we computed the basal kon for barnase and barstar, two of the most rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 30 publications
(92 reference statements)
1
44
0
Order By: Relevance
“…24 Third, we applied the weighted ensemble (WE) path sampling strategy, 2527 which has been demonstrated to be orders of magnitude more efficient than standard Brownian dynamics simulations in generating pathways and rate constants for protein binding processes. 28 Full details of the protein model, simulations, and analysis are below.…”
Section: Methodsmentioning
confidence: 99%
“…24 Third, we applied the weighted ensemble (WE) path sampling strategy, 2527 which has been demonstrated to be orders of magnitude more efficient than standard Brownian dynamics simulations in generating pathways and rate constants for protein binding processes. 28 Full details of the protein model, simulations, and analysis are below.…”
Section: Methodsmentioning
confidence: 99%
“…Several years later, the WE strategy was proven to yield continuous pathways and rate constants in a rigorous manner for any type of stochastic dynamics, including Monte Carlo, BD, and MD, thereby highlighting the generality of the strategy (70). Regardless of the type of dynamics or scale of the system, numerous studies have demonstrated that the WE strategy exhibits significant super-linear scaling in estimating observables; that is, quantities such as rate constants can be estimated with orders of magnitude fewer overall computing resources compared to standard parallelized simulations because WE-spawned trajectories can be focused on sampling bottlenecks (3, 17, 21, 22, 53, 55, 69, 75). Given this efficiency, there has been a resurgence of interest in the WE strategy over the past decade, resulting in the successful generation of pathways and calculation of rate constants for long-timescale processes that would otherwise be infeasible to simulate.…”
Section: Applicationsmentioning
confidence: 99%
“…Using flexible molecular models that reproduce the molecular shapes, electrostatic potentials, and diffusion properties of all-atom models, the WE strategy in combination with the Northrup-Allison-McCammon (NAM) approach (48) has reproduced the experimental k on for wild-type and mutant pairs of the barnase and barstar proteins (55). Notably, this study reported highly efficient simulation of the slow association between the exact hydrophobic, uncharged isosteres of the proteins, yielding the basal k on —a quantity of fundamental interest for determining the extent to which electrostatic interactions enhance the k on of the wild-type proteins.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations